Investigating Tensile Behavior of Sustainable Basalt–Carbon, Basalt–Steel, and Basalt–Steel-Wire Hybrid Composite Bars - Mirdarsoltany, Mohammadamin (2021)
One of the main disadvantages of steel bars is rebar corrosion, especially when they are exposed to aggressive environmental conditions such as marine environments. One of the suggested ways to solve this problem is to use composite bars. However, the use of these bars is ambiguous due to some weaknesses, such as low modulus of elasticity and linear behavior in the tensile tests. In this research, the effect of the hybridization process on mechanical behavior, including tensile strength, elastic modulus, and energy absorbed of composite bars, was evaluated. In addition, using basalt fibers because of their appropriate mechanical behavior, such as elastic modulus, tensile strength, durability, and high-temperature resistance, compared to glass fibers, as the main fibers in all types of composite hybrid bars, was investigated. A total of 12 hybrid composite bars were made in four different groups. Basalt and carbon T300 composite fibers, steel bars with a diameter of 6 mm, and steel wires with a diameter of 1.5 mm were used to fabricate hybrid composite bars, and vinyl ester 901 was used as the resin. The results show that, depending on composite fibers used for fabrication of hybrid composite bars, the modulus of elasticity and the tensile strength increased compared to glass-fiber-reinforced-polymer (GFRP) bars by 83% to 120% and 6% to 26%, respectively. Moreover, hybrid composite bars with basalt and steel wires witnessed higher absorbed energy compared to other types of hybrid composite bars.